PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS DAN NHT TERHADAP PRESTASI IPS EKONOMI SISWA DITINJAU DARI MOTIVASI BELAJAR - Sulistyowati, Endar; Joyoatmojo, Soetarno; Harini, Harini (Jurnal Pendidikan Insan Mandiri, 2017)
AbstractThis study to know: 1) The effect of the cooperative learning models of NHT type and the cooperative learning models of TSTS type on the learning achievement in Economy Social Science; 2) the effect of the students high, moderate and low level learning motivation on the learning achievement in Economy Social Science; and 3) the interaction of effect between the cooperative learning models and the students learning motivation the learning achievement in Economy Social Science. This research is a quasi-experimental, 2x3 factorial design. The population in this study are all Junior High School in Karanganyar. The sampling technique used was cluster random sampling. The sample in this study amounted to 66 students include 32 students of eight grade of SMPN 5 Karanganyar as experimental class and 34 students of eight grade SMPN 2 Jaten as the control class. The trial results were analyzed with the learning achievement test content validity test, reliability test, level of difficulty, different power and internal consistency. The validity test of each test items used by Product Moment correlation technique of Kark-Pearson at the level of 5%. Instrument reliability test using Cronbach Alpha formula. By using SPSS 22 figure reliability coefficient of 0.7. Test requirements analysis consists of tests of normality and homogeneity test. Normality test is done using the Kolmogorov-Smirnov Lilliefors method and the results were normal distribution of data across groups. Levene homogeneity test using the test and the result is a homogeneous whole group of data variance. The data analysis technique for testing to test the hypothesis in this study is an analysis of variance followed by a two-lane Scheffe test. Hypotheses were analyzed with SPSS for windows at significant level of 0.05.The results showed that: 1) student achievement that used NHT model better than direct TSTS model and p-value anava test respectively for 0.000 and 0.000; 2) student achievement that has a high motivation better than the learning achievement of students who have high levels of motivation medium and low, and p-value anava test respectively for 0.000 and 0.012; 3) there is a interaction between the learning model and level of learning motivation to student achievement,and p-value anava test respectively for 0.000 and 0.022. Keywords: NHT, TSTS, learning motivation, learning achievement